Asset quality concern and its effect on performance of public and private sector banks in India : an empirical assessment - Mohanty, Birajit; Mehrotra, Shweta (Penerbit Universiti Kebangsaan Malaysia, 2021)
In fast growing economies such as India, banks are seen as financial wagons that support financial progress and also have the additional responsibility to achieve the socio-economic goals of the government. The issue of the recent corrosion in the asset quality of commercial bank is a major distress for the entire banking industry as there has been significant rise in the level of non-performing assets (NPAs) which are considered as a key parameter for assessing performance of banks. In this paper, the asset quality refers to the NPAs in Indian banking sector. This study seeks to examine the influence of NPAs on the performance of banks in India. The study is based on the secondary data of 48 scheduled commercial banks which includes 27 public sector banks and 21 private sector banks for the period 2007-08 to 2017-18, which was gathered and compiled from the published reports of Reserve Bank of India. In this study, NPAs to Gross Advances, Gross NPAs to total assets, Net NPAs to Net Advances and Net NPAs to Total Assets are used as proxy variables for non-performing assets whereas Return on Asset and Return on Equity are used as proxy variables for the performance of banks. The study found that NPAs adversely impacted the performance of banks irrespective of the category of banks. However, the Public Sector Banks were affected more by the augmented level of deteriorating assets quality than their private counterparts.